Manifestation of Crohn's disease in a young woman during the course of treatment for severe form of chronic plaque psoriasis with etanercept. Issue 4 (18th February 2014) - Tichy, Martin; Hercogova, Jana
Abstract With the growing number of patients with immune‐modulated diseases treated with tumor necrosis factor (TNF) alpha inhibitors, we are more frequently encountering the occurrence of so‐called paradoxical drug reactions. These are basically situations where during the course of the treatment of one disease, the manifestation of another with similar etiopathogenesis occurs, although under normal conditions this newly developed disease responds well to treatment with TNF alpha inhibitors and is indicated for this treatment. Skin reactions are most frequently recorded in the form of induced psoriasis and psoriasiform exanthems. A less common paradoxical reaction is the induction of Crohn's disease, which is most often described in association with the treatment of inflammatory joint diseases with etanercept. We present a case of induction of Crohn's disease during therapy with etanercept, where the primary disease being treated was psoriasis. In the literature, similar cases have only been described sporadically.